Impact of Annual Appraisal Processes on Nurses’ Job Performance and Satisfaction: A Systematic Review - Jincy Joseph; Bejoy Varghese (علوم بهداشتی ایران)
Background and Purpose: Nursing performance significantly influences healthcare outcomes. Given the essential role of performance appraisals (PAs) in professional development, this review aims to systematically evaluate the impact of annual appraisals on nurses’ job performance and job satisfaction, highlighting the effective appraisal systems in nursing. Materials and Methods: This systematic review employed the Matrix Method and adhered to PRISMA guidelines. A comprehensive literature search was conducted across six databases: PubMed, CINAHL, Cochrane Library, Scopus, PsycINFO, and ScienceDirect. The search was restricted to English publications from 2012 to 2022. Specific keywords and MeSH terms related to nursing performance, PAs, and job satisfaction were used. After removing duplicates and screening titles and abstracts, full-text articles were assessed against predefined inclusion and exclusion criteria. Studies were included if they involved nurses, focused on annual appraisals, and used a cross-sectional design. Results: This search yielded 764 abstracts, which, after rigorous screening, led to 112 full-text articles being assessed. Ultimately, 11 cross-sectional studies were selected for detailed analysis. The analysis revealed that structured annual appraisal processes positively influence nurses’ job performance and satisfaction by providing clear performance expectations, constructive feedback and fostering a supportive environment for professional growth. Conclusion: This review underscores the importance of well-structured appraisal processes that provide clear expectations and constructive feedback to enhance nurses’ job performance and satisfaction. However, these conclusions are primarily drawn from the specific settings studied and may not be applied to all healthcare contexts. Future research should identify optimal appraisal strategies and examine their applicability across diverse healthcare environments. Healthcare institutions should prioritize refining appraisal processes to enhance open communication, professional development, and high-quality nursing care.